Guide to Load Analysis for Durability in Vehicle Engineering. - Johannesson, P. (Automotive Series., 2013)
The overall goal of vehicle design is to make a robust and reliable product that meets the demands of the customers and this book treats the topic of analysing and describing customer loads with respect to durability. Guide to Load Analysis for Vehicle and Durability Engineering supplies a variety of methods for load analysis and also explains their proper use in view of the vehicle design process. In Part I, Overview, there are two chapters presenting the scope of the book as well as providing an introduction to the subject. Part II, Methods for Load Analysis, describes useful methods and i.